Low- and High-Pressure Membrane Separation in the Production of Process Water for Coke Quenching - Anna Trusek; Maciej Wajsprych; Andrzej Noworyta (Membranes, 2021)
Although the time for operating mines and coking plants in many countries is coming to an end due to climate change, we must still ensure that the pollution generated by this source of the economy is minimized. Despite the several stages of treatment of the coke-oven effluent, completed with nitrification and denitrification processes preceding final sedimentation, the stream obtained does not meet the requirements of water for coke quenching. That is why the stream after biodegradation and sedimentation was treated on membrane units to ensure water reusing in the coking plant. As the subjected stream contained both solid and dissolved pollutants, a two-stage system was proposed: low- and high-pressure membrane filtration. Industrial modules were tested on pilot units operating under industrial plant conditions. In the case of the ultrafiltration process, all the tested ultrafiltration modules fulfilled the primary task. All of them separated almost completely the turbidities present in the stream, which would have disturbed the operation of the high-pressure plant. Considering the decrease in permeate flux and the possibility of cleaning, a PCI membrane made of PVDF tubes with a diameter of 12.5 mm and pore size of 20 μm was selected. Regarding the high-pressure membrane filtration, the reverse osmosis membrane was significantly better in the removal efficiency of both organic and inorganic dissolved substances. An operating pressure of 3 MPa was chosen for the system. Hence, membrane processes, which are not used as stand-alone treatment units for coke-oven effluents, function well as a final treatment stage.